Creating a new, sustainable mindset through responsible consumption: A case study of the international chain of sustainable restaurants - Marek Seretny; Deepika Gaur; Katarzyna Sobczyk; Maya Kaabou (Foundations of Management, 2021)
This paper presents research conducted in the United Arab Emirates with the management of Bareburger, the chain of sustainable restaurants, as well as among its clients. In our project, we are interested in the relation between the offer of sustainability and the culture of conscious consumption. The opinions of industry experts and customers collected in an interview session are analyzed to derive the answer to the research questions. The research focuses on finding the possibility of changing the mindset and habits of consumers and creating an impact on consumer behavior by offering a responsible and sustainable nutrition model. An experiment was conducted to analyze the effect of sustainable restaurants on consumer culture in terms of cultivating healthy food habits. In our case study, we analyze Bareburger, a healthier fast-food chain that originated in the United States, which took the concept of sustainability to a completely new level, from ideation to implementation. Observing this process, we checked whether the unhealthy eating habits that we observe in the Middle East can be changed through the carefully composed model of a responsible restaurant.
Keywords: M3; M30; M31; M39; 650; sustainable lifestyle; mindset; conscious consumption; organic; health-conscious consumers; sustainable marketing